2022
DOI: 10.1039/d2py00588c
|View full text |Cite
|
Sign up to set email alerts
|

New block poly(ether sulfone) based anion exchange membranes with rigid side-chains and high-density quaternary ammonium groups for fuel cell application

Abstract: We report a series of novel poly(ether sulfone) based anion exchange membranes (AEMs) with relatively good stability due to their rigid side-chains and heterocyclic quaternary ammonium groups. The AEMs show appropriate performance in AEM fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 74 publications
0
13
1
Order By: Relevance
“…Furthermore, XPS was used to study the structural analysis of block copolymer-based PES and quaternized with high-density QAs (MPy) and crosslinked with a lengthy rigid side chain. 321 In this study, block copolymer PES that had been MPy treated showed that C-N and N 1s at 399.2 and 401.7 eV were obtained, respectively, by the polymer backbone and QAs (MPy). Only C-Br peaks at 70.9 eV were visible in the brominated PES polymer, while an additional peak at the Br ion at 67.1 eV was visible aer functionalization with MPy.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 63%
“…Furthermore, XPS was used to study the structural analysis of block copolymer-based PES and quaternized with high-density QAs (MPy) and crosslinked with a lengthy rigid side chain. 321 In this study, block copolymer PES that had been MPy treated showed that C-N and N 1s at 399.2 and 401.7 eV were obtained, respectively, by the polymer backbone and QAs (MPy). Only C-Br peaks at 70.9 eV were visible in the brominated PES polymer, while an additional peak at the Br ion at 67.1 eV was visible aer functionalization with MPy.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 63%
“…56,57 However, this peak does not appear in the spectrum of ionized ionomer Q-BOC-OEC-1/1. Conversely, a peak attributed to the bromide ions (Br − ) appears at the binding energy of 66−68 eV, 56,57 indicating that the alkyl bromine in the copolymer is basically completely ionized with trimethylamine. Figure S3b shows the energy spectra of the chloride ion in the unionized copolymer and the ionized Q-BOC-OEC-1/3.…”
Section: Structural Characterizationmentioning
confidence: 95%
“…However, unlike AFM tests under conventional conditions, where the membrane can absorb moisture in the air to enlarge the hydrophilic region, TEM is tested under vacuum conditions, so the size of the hydrophilic region is significantly smaller than that in the corresponding AFM image. 50,57 3.5. Thermal and Mechanical Properties.…”
Section: Hydroxide Ionic Conductivitymentioning
confidence: 99%
“…Hence, many studies reported that the combination of cross-linking with high IEC could realize a balance between conductivity and swelling. However, there is a tradeoff between conductivity and mechanical property for performing the cross-linking reactions. It has been found that the ion transport could be promoted via constructing continuous ion transport channels with suitable microphase separation by using polymers such as comb-typed polymers, block copolymers, side chain polymers, etc. However, the formation of the microphase separation structure is still closely relevant to the IEC of the polymer.…”
Section: Introductionmentioning
confidence: 99%